Case Report: Unusual Peritoneopericardial Diaphragmatic Hernia in an 8-Month-Old German Shepherd Dog, Associated With a Pericardial Pseudocyst and Coexisting Severe Pericardial Effusion Resulting in Right-Sided Heart Failure - Hennink, Imke; Düver, Pia; Rytz, Ulrich; Meneses, Felix; Moioli, Melania; Adamik, Katja-Nicole; Kovačević, Alan (Frontiers in Veterinary Science, 2021)
Abstract Objective: To describe an unusual peritoneopericardial diaphragmatic hernia (PPDH) in an 8-month-old German Shepherd Dog, associated with a pericardial pseudocyst and coexisting severe pericardial effusion resulting in right sided heart failure. Case summary: An 8-month-old, male, intact, German Shepherd Dog, was referred for ascites. Echocardiography revealed a severe pericardial effusion with a cyst-like structure within the pericardium and consequently decompensated right sided heart failure. The ascites was secondary to right sided heart failure (cardiac tamponade). Computed tomography (CT) of the thorax and abdomen was performed and showed peritoneal-pericardial-diaphragmatic-hernia (PPDH) with severe pericardial effusion and presence of a pericardial cyst-like structure; xyphoid cleft and y-shaped seventh sternebra; mild thickening along the cranioventral abdominal wall consistent with scar tissue from the previous umbilical hernia surgical repair. During surgery the PPDH was corrected, and it was revealed that the remnant of the umbilical cord passed through it, into the pericardium. The cyst-like structure was successfully resected and send for pathology. Histopathology showed signs of a chronic suppurative inflammation, with absence of a mesothelial or endothelial wall layer, thus consistent with a pseudo-cyst. Based on tomographic and surgical findings, it is suspected that the pseudo-cyst, together with the pericardial effusion, evolved by an inflammation of the remnant of the umbilical cord during the umbilical hernia surgical repair 1 month prior to presentation. The underlying PPDH most likely favoured the development of the pericardial pseudo-cyst. However, due to prior antibiotic therapy initiated by the private vet, an infectious origin cannot be ruled out completely. New or unique information provided: There are a few case reports describing PPDH and/or pericardial pseudo-cysts in veterinary patients, but the current case report is unique, since it describes PPDH associated with a pericardial pseudo-cyst and coexisting severe pericardial effusion resulting in cardiac tamponade. As far as the authors know, such a case has not been described in veterinary medicine before.